Numeria: An RME-Based Interactive Multimedia Prototype to Improve the Numeracy Skills of Students with Dyscalculia - Siti Nurhidayati; Riawan Yudi Purwoko; Puji Nugraheni (Jurnal Riset Pendidikan Matematika, 2026)
The numeracy skills of Indonesian students remain a major challenge, especially for dyscalculic students in learning mathematics. One of the contributing factors is the limited availability of inclusive learning media that provide interactive and contextual experiences, making it difficult to connect mathematical concepts with real-life situations. This study aims to conduct a needs analysis for the development of a learning medium called Numeria, an RME-based multimedia prototype designed to improve the numeracy skills of dyscalculic students in learning mathematics in elementary school. This study uses the ADDIE development method, focusing on the analysis and design stages. Data were collected through interviews, observations, and questionnaires involving 48 dyscalculic students in fifth grade at elementary schools in Central Java. Data analysis was conducted descriptively. The results of this study indicate that students with mathematical dyscalculia need interactive learning media that can present mathematical concepts more concretely and contextually. Teachers also expressed the need for innovative media that connect abstract mathematics with everyday contexts relevant to students' experiences. The integration of RME principles into multimedia is expected to increase motivation, engagement, and deeper understanding, thereby contributing to the improvement of dyscalculic students' numeracy skills. These findings provide a solid foundation for further design and development related to Numeria as an interactive and inclusive mathematics learning medium.